FASILITAS BREAKOUT AREA SEBAGAI UPAYA TERCIPTANYA SOCIAL SUSTAINABILITY PADA KARYAWAN BANK BUMN - Mediva Dyah Fajriani; Ratri Wulandari (Universitas Trisakti, 2022)
Social sustainability is now often known as an important strategy in the running of a corporation in developing its human resources, including Bank BUMN. This banking company is currently still facing problems in the form of an overworked culture for its employees which causes stress and decreases work productivity. This study analyzes the needs and activities of Bank BUMN employees to provide work facilities that can be a way out of these problems. The research method used is a mix-method that tends to be descriptive with analysis showing that breakout area facilities can be a step in fulfilling employee job satisfaction and creating social sustainability in the work environment of Bank BUMN.